PENGARUH PENDEKATAN SAINTIFIK TERHADAP PRESTASI BELAJAR PKN DITINJAU DARI SIKAP DEMOKRASI SISWA KELAS V GUGUS I KECAMATAN ABANG - Ni Ketut Erna Muliastrini (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2019)
This study aims to determine the effect of the scientific approach to Civics learningachievement in terms of student democratic attitudes. This research is a quasi-experimentalstudy with the design of The Posttest-Only Control-Design Group. The study population was allfifth grade students of Elementary School I, Abang Subdistrict, totaling 147 students. A total of100 students were selected as samples determined by group random sampling technique. Dataon democratic attitudes were collected by questionnaires and learning outcomes using multiplechoice tests. Data were analyzed using ANA-B ANOVA analysis assisted by SPSS 17.00 forWindows. Results showed that: First, there were differences in PKN learning achievement betweenstudentswhotooklessonswithscientificapproachesandstudentslearningwithconventionallearningmodelsinclassVofClusterIDistrictBrother.PKNlearningachievementofstudentswhotakelessonswithascientificapproachisbetterthanyourPKNlearningachievementofstudentswhotakelessonswithconventionallearning.Second,thereisaninteractionbetweentheapplicationofthelearningmodelandtheDemocraticAttitudeofstudentstowardsPKNlearningachievementinclassVofClassIofAbangDistrict.Forstudentswhohaveahighdemocraticattitude,PKNlearningachievementofstudentswhotakelessonswiththescientificapproachisbetterthanconventionallearning.Third,thelearningoutcomesofstudentswhohavehighdemocraticattitudeswhotakelessonswiththescientificapproacharebetterthanyoustudentswhotakelessonswithconventionalmodels.Fourth,forstudentswhohavealowdemocraticattitude,thereisnodifferenceinlearningachievementbetweenstudentswhotakelessonswiththescientificapproachandstudentswhotakelessonswithconventionallearning.